2002
DOI: 10.1002/gps.736
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of behavioural and psychological symptoms of probable Alzheimer's disease

Abstract: Activity disturbance is common and persistent in early AD. Paranoid and delusional ideation shows moderate persistence and depressive symptoms infrequently last longer than a year. These findings may have clinical relevance for the pharmacological and non-pharmacological management of BPSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 24 publications
(38 reference statements)
7
92
1
3
Order By: Relevance
“…Longitudinal studies using assessment scales other than the NPI demonstrate heterogeneity in the course of symptoms and that NPS may arise at any stage of dementia. However, agitation seems to be the most persistent symptom and shows an increasing severity with disease progression in a majo-rity of the studies, whereas the persistence of psychosis and depression shows greater variability (27)(28)(29)(30). It should be noted that apathy was investigated rarely in these studies.…”
Section: Nps In Persons With Dementia Attending Outpatient Clinicsmentioning
confidence: 83%
“…Longitudinal studies using assessment scales other than the NPI demonstrate heterogeneity in the course of symptoms and that NPS may arise at any stage of dementia. However, agitation seems to be the most persistent symptom and shows an increasing severity with disease progression in a majo-rity of the studies, whereas the persistence of psychosis and depression shows greater variability (27)(28)(29)(30). It should be noted that apathy was investigated rarely in these studies.…”
Section: Nps In Persons With Dementia Attending Outpatient Clinicsmentioning
confidence: 83%
“…Previously, the presence of more severe noncognitive symptoms, such as elation, motor disturbances, hallucinations, delusions, and disinhibition, is described in conjunction with more advanced AD dementia. 2 Our sample suggests that this arc of noncognitive changes begins in preclinical AD dementia. Such a finding corroborates our previous study, which showed that depression scores and other behavioral symptoms monitored by the NPI-Q worsen faster among individuals with preclinical AD dementia at baseline as defined by CSF biomarkers.…”
mentioning
confidence: 79%
“…With progressive cognitive and functional decline in AD dementia, the presence of NPS is postulated to represent increased neurodegradation across neural systems. [2][3][4][5] Such NPS have been associated with worse prognosis, accelerated illness progression, increased use of services, and earlier institutionalization. 2 However, variable neuropsychiatric measures and clinical definitions have clouded the true incidence and progression of NPS in patients with AD.…”
mentioning
confidence: 99%
“…It is also important to note that changes in the central cholinergic system in AD may also contribute to a variety of adverse behavioral symptoms (i.e., in addition to cognitive deficits) such as depression, aggressive behavior, psychosis, and overactivity (Minger et al, 2000). These so called "noncognitive" symptoms of AD increase caregiver burden, significantly raise the direct costs of care, and result in earlier institutionalization (reviewed Eustace et al, 2002). A number of studies now indicate that the standard therapy for cognitive dysfunction in AD (i.e., the acetylcholinesterase inhibitors) are associated with improvement in a number of behavioral symptoms including depression, psychosis, agitation, and a delay in nursing home placement (reviewed, Cummings, 2003).…”
Section: Cholinergic-based Therapeutic Strategies (Present and Futurementioning
confidence: 99%